2019 7th Mediterranean Congress of Telecommunications (CMT) 2019
DOI: 10.1109/cmt.2019.8931382
|View full text |Cite
|
Sign up to set email alerts
|

QoE-based Performance Evaluation of Video Transmission using RPL in the IoMT

Abstract: Internet of Things systems can not successfully realise the notion of ubiquitous connectivity of everything if they are not capable to truly include multimedia things. In this paper, we investigate the feasibility of video streaming using RPL (Routing Protocol for Low Power and Lossy Networks) by focusing on the impact of radio duty cycling on the quality of received video and the energy footprint of the network. To do so, we adopt a low complexity compression technique and use Cooja simulator to carry out our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The achieved simulation results showed that the enhanced RPL outperforms the native RPL in terms of end-to-end delay, throughput, packet delivery rate and power consumption. A simulation based study of the feasibility of visual data transmission over the standard RPL is presented in [26]. By focusing on the impact of radio duty cycling on the received video quality as well as the network consumed energy, simulation results mainly showed that RPL along with ContikiMAC can not support realtime…”
Section: Multimedia Support Over Rplmentioning
confidence: 99%
See 2 more Smart Citations
“…The achieved simulation results showed that the enhanced RPL outperforms the native RPL in terms of end-to-end delay, throughput, packet delivery rate and power consumption. A simulation based study of the feasibility of visual data transmission over the standard RPL is presented in [26]. By focusing on the impact of radio duty cycling on the received video quality as well as the network consumed energy, simulation results mainly showed that RPL along with ContikiMAC can not support realtime…”
Section: Multimedia Support Over Rplmentioning
confidence: 99%
“…Due to the high rate video traffic that characterizes multimedia applications, we have used the null radio duty cycle (Nullrdc) mechanism on the Contiki OS MAC layer because it makes nodes to be awake all the time in order to receive and transmit video packets. Moreover, it has been proven in [26], that RPL under ContikiMAC can not handle realtime video transmission. However, to overcome the inefficiency of power consumption caused by this Nullrdc driver, harvesting energy mechanisms can be integrated at network nodes in order to balance the trade-off between quality of transmissions and the limited resources of WMSNs [5,6,50].…”
Section: Simulations Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the fact that RPL almost meets the requirements of LLNs to support scalar data transport, it remains difficult to handle real time streaming of video clips since it was mainly targeted to low data rate applications [14]. To allow for multimedia transport, new objective functions based on energy [4,27] or free bandwidth [8] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Such a Cloud-Fog-Edge architecture provides the processing support needed by the IoHT constrained devices. This way, IoHT technologies can contribute to improve performance, reduce costs and mitigate risk [12][13][14][15][16][17]. However, although the IoHT have been adopted to monitor people everywhere, there is a place where technology must be much more efficient due to its inherent criticality: the hospital.…”
Section: Introductionmentioning
confidence: 99%